Science interactions (Glencoe/McGraw-Hill, 1995)
Science is something that refuses to stay locked away in a laboratory. In both the science and society and the technology features, you'll learn how science impacts the world you live in today. you may also be asked to think about science-related questions that will affect your life fifty years from now.